2014
DOI: 10.1149/2.010409jss
|View full text |Cite
|
Sign up to set email alerts
|

Role of Self-Assembled Monolayers on Improved Electrical Stability of Amorphous In-Ga-Zn-O Thin-Film Transistors

Abstract: Self-assembled monolayers (SAMs) have been used to improve both the positive and negative bias-stress stability of amorphous indium gallium zinc oxide (IGZO) bottom gate thin film transistors (TFTs). N-hexylphosphonic acid (HPA) and fluorinated hexylphosphonic acid (FPA) SAMs adsorbed on IGZO back channel surfaces were shown to significantly reduce biasstress turn-on voltage shifts compared to IGZO back channel surfaces with no SAMs. FPA was found to have a lower surface energy and lower packing density than H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…30 Upon close inspection, even the ridges on the PDMS stamp were replicates of the grooves in the SU-8 master. Phosphonic acid has been used to tune the surface properties of metal oxide films; 18,20,[31][32][33] and for these studies, we used ODPA ink as the protective layers on top of the blanket ITO film. We found that the lCP ODPA transferred ink was continuous and provided excellent etch resistance to oxalic acid.…”
Section: Resultsmentioning
confidence: 99%
“…30 Upon close inspection, even the ridges on the PDMS stamp were replicates of the grooves in the SU-8 master. Phosphonic acid has been used to tune the surface properties of metal oxide films; 18,20,[31][32][33] and for these studies, we used ODPA ink as the protective layers on top of the blanket ITO film. We found that the lCP ODPA transferred ink was continuous and provided excellent etch resistance to oxalic acid.…”
Section: Resultsmentioning
confidence: 99%
“…core level spectra of the as-deposited film are fitted into three components (figure 6(a)) with their respective binding energies at 528.4, 530.0, and 531.4 eV. The low energy peak can be assigned to the lattice oxygen ions, the middle peak to the adsorbed hydroxyl ions, and the high energy peak to some contaminants as reported by Du et al 18 The area of the middle peak reduced (figure 6(b)) upon annealing at 400 o C in N 2 ambience, while it increased for the low and high energy peaks. A decrease in binding energy (0.14 eV) is also observed in middle peaks but there is no change in the low energy peak.…”
Section: B Electrical Characterizationmentioning
confidence: 91%
“…29,30 The obtained s and b values for both TFTs are summarized in Table 1. Because the DV TH values were in good agreement with the stretched exponential relationship, the charge-trapping mechanism could be concluded as the primary cause for the PBTS instabilities.…”
Section: 28mentioning
confidence: 99%